Model Sharing Benefit Agreement sebagai Instrumen Perlindungan Hukum Preventif dalam Pemanfaatan Ekspresi Budaya Tradisional di Indonesia - Tesya Adelia Putri; Gilbert Bastanta (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
Traditional Traditional Cultural Expressions (TCEs) constitute communal intellectual property that holds both cultural and economic value, thus requiring legal protection capable of guaranteeing the rights of indigenous communities as the custodians of these cultures. However, Indonesia’s legal framework has not yet comprehensively regulated the mechanisms for obtaining consent from indigenous communities and ensuring a fair distribution of benefits in the utilization of TCE, thereby potentially leading to exploitation, unequal bargaining power, and disputes between indigenous communities and the parties utilizing these resources. This study aims to analyze legal provisions regarding the resolution of disputes over the utilization of TBE and to formulate an ideal model for a Sharing Benefit Agreement (SBA) as an alternative dispute resolution mechanism. The study employs a normative legal methodology using legislative, conceptual, and case-based approaches. Primary and secondary legal sources were qualitatively analyzed through a literature review. The findings indicate that current regulations remain focused on administrative protection and have not adequately addressed mechanisms for community consent, benefit-sharing, or contractual relationships between indigenous communities and resource users. Therefore, this study proposes an SBA model based on the principles of justice, good faith, balance among the parties, recognition of cultural identity, and fair and equitable benefit sharing. The model includes provisions on Prior Informed Consent, Mutually Agreed Terms, benefit-sharing, protection of communal moral rights, and dispute resolution mechanisms as preventive legal safeguards.